Pengaruh Desain Magnet Pada Rotor Generator Dan Variasi Kecepatan Angin Terhadap Energi Listrik Yang Dihasilkan Oleh Turbin Angin Sumbu Horizontal Skala Mikro - Mohamad Ulil Albab; Husin Bugis; Herman Saputro (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
Energy use in Indonesia is increasing while energy reserves in Indonesia are running low. In an effort to meet energy needs in Indonesia, there must be the development of renewable energy sources by utilizing wind energy to be converted into electrical energy using a horizontal wind turbine generator. To optimize the wind turbine generator, you can change its parameters, one of which is by changing the design of the generator magnet. The method used in this study is an experimental method, where the variables used in this study are the design of the magnet skew, the design of the interior magnet and the design of the magnet surface. This research was conducted at wind speeds of 1 m/s to 5 m/s using a wind tunnel. Tests were carried out using 12 V and 24 V lamp loads and no-load tests to determine the power generated by each generator. The results of the research are the design of the magnet on the generator rotor and variations in wind speed affect the power produced by the wind turbine, the magnetic skew produces a power of 0.974 W, the interior magnet produces a power of 0.674 W and the surface magnet produces a power of 1.386 W. Tests without load and speed variations The wind affects the power produced by the wind turbine, where the power at the generator cannot be calculated. Tests with loading and wind speed variations affect the power produced by the wind turbine, where each loading test has various results such as when a load is given to the magnetic surface design at a wind speed of 5 m/s with a loading of 24 V producing a power of 1.386 W.